Value Generation in Software Projects: Lessons Learned from the Reimplementation of Design Thinking in a Technological Development Institute - Meireles, Maria Alcimar Costa; Afonso, Ádria; Rabaioli, Brunna Talita Vieira; Soares, Karen; Araújo, Lívia Lobão de; Lobão, Luana; Maldonado, Jose Carlos; Conte, Tayana (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2024)
Context: This paper reports the experience of re-implementing Design Thinking (DT) in a Technological Development Institute that faced potential closure due to the departure of its sponsors (funding companies). Following the departure of the sponsors, the Institute relocated its operations, resulting in a significant reduction of the team to 33 employees, alongside new hires focused on development. This transition led to losing the previous organizational culture, particularly in applying DT. Of the remaining 33 employees, 2 were designers, one of whom led the re-implementation of DT with new collaborators willing to engage in research and prototyping. Objective: We aim to present the experience and lessons learned from the re-implementation of DT in a Research and Development Institute that adopts agile practices in its software development process.Method: To collect the experience and lessons learned regarding the re-implementation of DT, we conducted interviews with four former employees directly involved in the process. Results: The results of this study indicate that DT can effectively provide a clear vision of what will be delivered at each development stage, understanding the problem and generating project solutions. Conclusion: This study revealed that the re-implementation of DT was motivated by the need to involve designers and the development team in the Discovery process. The re-implementation brought significant benefits, such as improved internal communication, a deeper understanding of client needs, and strengthened team cohesion. The main challenges were changing the clients’ mindset and demonstrating the value of DT to clients, managers, Product Owners, and the technical team.